Analisis Decision Support System Perbandingan Metode Smarter dan Saw Dalam Menentukan Pemilihan Staff Pegawai Terbaik Laboratorium Komputer - Nandri Marsan Sitinjak; Muhammad Zarlis; Roslina Roslina (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The best employees will make an agency to increase in its operations and can develop rapidly. However, relations on the part of an agency are still not optimal in selecting the best staff. Therefore, human resource management is needed in an agency with the selection of the best employee staff to spur staff morale in improving operations, dedication and performance in an agency, so that it becomes better, namely by creating a Decision Support System in selecting the best staff employees by using the Smarter and Saw method comparison method. The Smarter and Saw method is a decision-making method using multiplication to determine the value of a criterion, where the value for each criterion must be determined in advance with the weight of each criterion concerned. By utilizing the advantages and disadvantages of each method, the comparison of this method is able to give a value of 79.5 for the Smarter method, 93 for using SAW. Decision support systems using this comparison method can assist in the selection of the best employees and provide an alternative choice of ranking results